2006
DOI: 10.1007/s00066-006-1524-x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Chemotherapy after Chemoradiation Improves Survival of Patients with Locally Advanced Pancreatic Carcinoma

Abstract: Maintenance chemotherapy after chemoradiation for patients with locally advanced PaCa may significantly increase survival rates without severe side effects and is therefore recommended as standard treatment following chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The value and particularly the toxicity of additive chemotherapy before or after CRT have to be further assessed in studies. Combinations of CRT and chemotherapy reported median OS times of 13 - 15 months [24,64,67]. Currently this approach is further evaluated in the international phase III LAP07 trial randomising patients with LAPC who do not progress after four months of chemotherapy with gemcitabine between a CRT with concurrent capecitabine versus two more cycles of gemcitabine.…”
Section: Locally Advanced Tumoursmentioning
confidence: 99%
“…The value and particularly the toxicity of additive chemotherapy before or after CRT have to be further assessed in studies. Combinations of CRT and chemotherapy reported median OS times of 13 - 15 months [24,64,67]. Currently this approach is further evaluated in the international phase III LAP07 trial randomising patients with LAPC who do not progress after four months of chemotherapy with gemcitabine between a CRT with concurrent capecitabine versus two more cycles of gemcitabine.…”
Section: Locally Advanced Tumoursmentioning
confidence: 99%
“…d1, 29) in eleven patients [4] and after January 1998 of gemcitabine (300 mg/m 2 in 30 min i.v. d1, 8,22,29) and cisplatin (30 mg/m 2 in 30 min i.v., d1, 8,22,29) in 27 patients [8].…”
Section: Chemoradiationmentioning
confidence: 99%
“…The patients without subsequent resection were reported elsewhere [8]. The rate of resection did not depend on the chemotherapeutic regimen (5-FU and mitomycin 30.5% vs. gemcitabine and cisplatin 32%).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The value and particularly the toxicity of additive chemotherapy after CRT have to be further assessed in studies [11,26,30]. In these retrospective studies combinations of CRT and chemotherapy reported median overall survival times of 13-15 months.…”
Section: Locally Advanced Tumorsmentioning
confidence: 99%